2013
DOI: 10.1097/prs.0b013e3182a48b8a
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction following Nipple-Sparing Mastectomy

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
93
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(96 citation statements)
references
References 47 publications
1
93
2
Order By: Relevance
“…In addition, to date there have been no controlled clinical trials evaluating the oncological effectiveness of nipple-sparing mastectomy (NSM) vs traditional SSM surgery. In spite of the controversies involving risk of local relapse, some current clinical studies have shown that the NSM is a safe procedure for selected cases [11,[14][15][16]18,[23][24][25][26][27]29,30,[33][34][35][36][37][38][39]44,47,48] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to date there have been no controlled clinical trials evaluating the oncological effectiveness of nipple-sparing mastectomy (NSM) vs traditional SSM surgery. In spite of the controversies involving risk of local relapse, some current clinical studies have shown that the NSM is a safe procedure for selected cases [11,[14][15][16]18,[23][24][25][26][27]29,30,[33][34][35][36][37][38][39]44,47,48] .…”
mentioning
confidence: 99%
“…The satisfactory results are due to a close collaboration with the oncological surgical ed the technique for benign diseases, however he did not report the procedure for oncological objectives or as a risk-reduction alternative [10,11] . Recently, there has been an increase in clinical experience studies of NSM for breast cancer prophylaxis or early cancer treatment, evidencing revived interest in this surgical procedure [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][33][34][35][36][37][38][39][40][41][42][43][44] . In fact, there is evidence that NSM provides aesthetic advantages, with reduced need for further surgery and NAC reconstruction [15,17,[20][21][22]29,[33][34][35][36][37][38][39]…”
mentioning
confidence: 99%
“…We used the following key terms to search all databases: nipple-sparing mastectomy, inframammary fold, immediate reconstruction, skin flap necrosis, nipple necrosis, and reconstructive criteria. The literature reflects a wide range of nipple-areolar complex necrosis rates between 0-48% (Salgarello et al, 2010;Rusby, Smith, & Gui, 2010 Sacchini et al, 2006;Spear et al, 2011;Djohan et al, 2010;Crowe et al, 2004;Colwell et al, 2014;Salibian, Harness, & Mowlds, 2013;Endara, Chen, Verma, Nahabedian, & Spear, 2013 reconstruction, Gould et al (2013) found that their overall incidence of any (partial or total) nipple necrosis was 20% via a non-IMF approach. In a review of 64 NSM via various approaches, Wijayanayagam et al noted a total NAC necrosis rate of 20%, partial NAC necrosis 84%, and total skin-sparing skin flap necrosis of 17%.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison of two cohorts of total skin-sparing mastectomies that differed in extent of NAC involved in the incision illustrated that periareolar incisions involving more than 30% of the circumference of the areola are at an increased risk of NAC necrosis, and along with other variables, adjusting the incision contributed to a significant reduction in nipple necrosis rates from 20% to 5% (Garwood et al, 2009). Furthermore, in a comprehensive literature search that included 6615 NSM, incision types were divided into five categories: radial, periareolar/circumareolar, inframammary, mastopexy, and transareolar, and found to have nipple necrosis rates of 8.83, 17.81, 9.09, 4.76, and 81.82%, respectively (Endara et al, 2013). Several other studies similarly corroborate these substantial differences in rates of NAC necrosis based on incision placement, with the IMF approach having the lowest rate of complication (Salgarello et al, 2010;Colwell et al, 2014;Endara et al, 2013;Chen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation